CONSERVE EPITOPES OF INFLUENZA VIRUS INDUCE INNATE AND ADAPTIVE IMMUNE RESPONSES TO PRODUCE SPECIFIC ANTIBODY AGAINST M2E PROTEIN - Mansyur, I -; Soemitro, S -; Subroto, T -; Soedjanaatmadja, U.M.S. - (Bionatura, 2014)
The existing vaccines against influenza are based onthe generation of neutralizing antibody primarilydirected against surface protein, haemagglutinin(HA) and neuraminidase (NA). However, antigenicdrift and occasional shift of these two membraneglycoproteins, HA and NA, make vaccine productioncumbersome and necessitate yearly revision ofthe vaccine seed strains by the World HealthOrganization. For these reasons, many investigatorshave often tried to look at the possibility of generatinga universal vaccine useful against more than oneinfluenza strain. The objective of research was toobtain an alternative antigen as vaccine candidatefor universal flu vaccination, instead of HA and NAcomponents. In this study, we use conserved epitopeM2e which is consist of three major componentsuch as N-terminal M2e2-24 (24 amino acids),transmembrane(59 amino acids) and C-terminal (19amino acids). We design two components of antigen,linier and branched structures. The antigens thenformulated with aluminium hydroxide gel comparedto FCA/IFA adjuvant. These vaccines were testedtheir immunogenicity, and the potency to mature thedendritic cells for stimulating either CD8+ T cell orantibody-mediated immune responses. The antibodytitre and the maturity of dendritic cell indicated bycytokines concentration such as; IFN-ã, IL2 and IL4were measured by ELISA test.The result of researchshowed that the conserved epitope of Me2 2-16 whenincorporated with P25 protein from canine distempervirus (linear structure) in alhydrogel adjuvant hasgreater potential to produce anti-M2e antibodiesthan in Freund adjuvant. Alhydrogel adjuvant hada stronger effect than Freund adjuvant. Alhydrogelalso stimulate the release of IL-2 and IL-4.Keywords: Epitopes, innate and adaptive immuneresponses, M2e-protein, haemagglutinin (HA),neuraminidase (NA), adjuvant.